Üküdar'ın Vakıf Eser Kültür Mirası Ve Korunması İçin Öneriler - Ekimci, Betül Gelengül (Fen Bilimleri Enstitüsü, 2012)
Üsküdar antik döneme uzanan tarihiyle İstanbul’un Anadolu yakasındaki en önemli yerleşmelerinden biridir. Osmanlı döneminde Üsküdar İstanbul’un üç yönetim merkezinden biri olarak Boğaz siluetini ve İstanbul’u taçlandıran tarihi çehresini 15. ve 19. yüzyıllar arasında kazanmıştır. İstanbul’un Anadolu ile bağlantısını sağlayan iskele civarında ve kervan yolu üzerinde, başta sultanlar ve aileleri tarafından cami, medrese, imaret, kervansaray, hamam, han ve dükkânlardan oluşan hayır tesisleri kurulmuş, zamanla üst düzey yöneticiler ve kentin ileri gelenlerince yaptırılan vakıf tesisler ile Üsküdar imar edilmiştir. Üsküdar’ın günümüze ulaşan tarihi anıtlarının çoğu vakıf yoluyla yapılmıştır. Üsküdar tarihinin önemli bir bileşeni olan vakıf kökenli kültür mirası daha iyi bakılmayı ve yönetilmeyi hak etmektedir. Vakıf eser kültür varlıklarının ayrıntılı olarak ele alınmaları, taşıdıkları ulusal ve evrensel değerlerin ortaya konması, korunmaları ve sürdürülebilmeleri yönünde önemlidir.Bu çalışmada Üsküdar’daki Osmanlı dönemi vakıf eserlerin yapıldıkları dönemden itibaren geçirdikleri değişimleri anlamaya çalışmak ve günümüzdeki durumlarını belgelemek amaçlanmıştır. Günümüze ulaşan örnekler tek tek yerinde incelenerek değişimin boyutları ortaya konmaya çalışılmış ve eserlerin özgünlükleri değerlendirilmiştir. Üsküdar, üzerine sayısız kitaplar yazılmış olmasına karşın, belli bir dönemdeki yüzünü, dokusunu ve evrimini kavramaya çabaladığımız anda karşımıza cevap bekleyen sorular ve yeni araştırma konuları sunan zengin bir coğrafyadır. 15. yüzyıldan 20. yüzyıla uzanan tarih aralığında, çeşme gibi küçük yapılardan, anıtsal külliye yapılarına uzanan vakıf eserlerin geniş yelpazesi içinde, Üsküdar’ın değişen yüzünü okumaya çalışmak şaşırtıcı deneyimleri birlikte getirmiştir. Üsküdar’ın tarihi mirasını temsil eden, kent dokusunun gelişimine yön veren vakıf eserlerin geçirdikleri süreç, onlara yapıtı ortaya çıkaran koşullardan ve yapıldıkları dönemden bağımsız bir kimlik kazandırmıştır. Ama uzun tarih yolculuğu içinde değişen var olma koşulları, yapıların önemini hiç hafifletmiyor. Tamamen yok olan veya bütünüyle yenilenen örnekler bir yana bırakıldığında, yapılar üzerinde geçmişin izleri hala varlığını koruduğundan, geçmişi ve geleceği birleştirmek, birbirini izleyen, birbirini içeren, değişimleri korumakla mümkün olabilir. Fakat diğer taraftan, yapının tarihi, fiziksel ve hatta sosyal yapısını zedeleyen niteliksiz kabukları doğru ayıklamak, özgün mimari karakterlerini ortaya çıkarmak, vakıf eserleri, bundan sonraki süreçte yeni müdahalelerle zedelenmeyecek evrensel bir maddi varlık olarak kabul etmenin ilk adımı.

Üsküdar situated on the Asian part of the Bosphorus is an integral part of Cultural Landscape Site of Istanbul. Starting with the fifteenth century, Üsküdar was inhabited by the Ottomans. During the Ottoman period Üsküdar’s importance continued. Üsküdar is exceptional with its position across the Historic Peninsula and Bosphorus views. The hills of Üsküdar commands one of the finest views of the old city, Haghia Sophia Topkapı Palace and the Blue Mosque from the Asian side. The Asian side of the city is also very impressive at sundown with its sparkling window glasses. The silhouette of Uskudar has been the subject of many famous songs and poems. Üsküdar also incorporates important elements from the long history of the city. Recent excavations at Uskudar harbour revealed interesting archaeological finds about the Byzantine past of this district. Starting with the fifteenth century, Sultans and high ranking officials had their summer palaces overlooking the Bosphorus and wide green areas were allocated for recreation. Until the twentieth century caravans which started their way to the East commenced their travel at Uskudar. In nineteenth century railways going to Bagdad and Hajj were established, starting from Haydarpasa on the outskirts of Uskudar. Among the rich cultural heritage of Uskudar, waqf buildings (pious foundation), donated by charitable people, have played important social, economical and cultural role in the development of urban life. The donators vary from ordinary citizens to the sultans and members of their families. The kind of waqf buildings also varies from modest public fountains which provided free water to the passerby, to imperial mosques; public kitchens serving students and the needy, libraries, dervish lodges providing free shelter for guests, hospitals curing the ill. Üsküdar has a rich collection of waqf buildings. Most historic monuments, mosques, medreses, and caravanserais are waqf property. The prominent waqf establishments in Üsküdar started with Rum Mehmed Paşa Complex which was established in 1470 and continued with Mihrimah Sultan, Kösem Sultan, Ahmediye, Yeni Valide, Ayazma, and Selimiye architectural complexes in the following centuries. The presence of these monuments determines the past and the future identity of the urban area. Studying and documenting these monuments is important as the first step in planning for the protection of the cultural heritage of Üsküdar. In 1924, just after the establishment of the Turkish Republic, all waqf buildings in Üsküdar were surveyed. Their condition and location was recorded. This document is kept at the Ismail Hakki Konyalı Library which belongs to the Istanbul Regional Directorate Waqf. It provides valuable information as first hand source. Since 1924, several of the buildings on this list have been lost due to construction of new roads or neglect. Several have lost their values and authenticity because of bad restorations. After 1950’s, rapid population growth and migration to Üsküdar have resulted in urban sprawl in historic town. Together with the changes of the social composition of historic urban centre, man-made damage and misuse of buildings lead to further damages. Especially tombs and fountains are exposed to natural damage. After losing the original function, most of the dervish lodges were deserted, they are completely neglected and falls into disrepair. Today those buildings are administered by the General Directorate of Waqf. Also waqf properties preservation is the responsibility of the General Directorate of Waqf. The diversity and the vast number of historic waqf buildings in Uskudar make it a gigantic task on the part of the General Directorate of Waqf to carry out a successful program for the maintenance and restoration of historic complex and monuments. In recent years thanks to increased budget of General Directorate of Waqf, restoration works have gained acceleration. As the survey of cultural heritage in Üsküdar is not yet completed, essential repair priorities can not be determined, serious loss of damaged buildings continues. The study started with the defining the boundaries of study area. Adresses recorded in the 1924 list had changed due to new road construction, merging quarters and administrative arrangements. Historic documents, old maps, city guides and other historic records were referenced to update adresses information. Completed in 1924-1935, Pervititich maps are an important work in terms of understanding former settlements and defining the study boundaries. These maps, by showing the material, floor numbers and function of buildings are permited a detailed study. Data structure including old street names can be seen on the edge of the maps. Thus, it has become possible to find adress information of altered or lost historical buildings. Another source utilized the names of old streets and neighborhoods is Istanbul City Guide printed in 1934 by the Municipality of Istanbul. This guide shows the main ways of Üsküdar central area in 1/10000 scale map. The study area captures 40 quarters located in historic core of Üsküdar. These are Kaptan Paşa, Ayazma, Kara Davut Paşa, Salacak, Mirahur, Gerede, Toygar Hamza, Tenbel Hacı Mehmet, Ahmet Çelebi, Selman Ağa, Gülfem Hatun, Evliya Hoca, Hacce Hesna Hatun, Solak Sinan, Kefçe Dede, Selami Ali Efendi, Tavaşi Hasan Ağa, Selimiye, İhsaniye, Kazasker Ahmed Efendi, Murad Reis, Bulgurlu Mescid, Arakiyeci Hacı Cafer, Arakiyeci Kacı Mehmed, Hayreddin Çavuş, Pazarbaşı, Durbali, Valide-i Atik, Aşçıbaşı, Debbağlar, Çakırcı Hasan Paşa, Sinan Paşa, Kısıklı, Dağ Hamamı, Rum Mehmet Paşa, Şemsi Paşa, Hamza Fakif, Altunizade quarters and Ümraniye, Bulgurlu villiges. According the list of 1924 waqf property in Üsküdar can be classified as religious buildings (mosques, dervish lodges and tombs), caravanseraies, hospitals, medreses, primary schools and libraries, foundations related with water such as fountains, wells, water tanks, toilets and timber houses for waqf staff, graveyards, and historic gardens. Within the framework of the study all waqf property, recorded at the 1924 list, were marked on Pervititch maps. For this purpose, Pervititch maps belong to Üsküdar region in 1/4000 scale are merged after scanning. To indicate the original function and current condition of waqf buildings, icons were prepared by using colors and abbreviations. The first step of the study consisted in documenting waqf buildings current situations by examine on site and photographs. For the proposals in the progressive stage, database that will allow to analyze all waqf building s priority issues is needed. To facilitate this work, temporary survey documents was prepared. Besides basic information (name, location, date, construction techniques, materials, protection status, related publications, etc.) about monuments, all the visible damages were recorded on survey. Historic documents including drawings, photographs and reports were inspected in order to reveal interventions as well as changes in surrounding urban areas. Besides, public surveys were executed with waqf staffs to understand the preservation problems. By using these sources, the physical conditions of waqf property were evaluated with in the scope of not only essential repair priorities but also values and authenticity as affirmed in The Charter of Venice and the Nara Document. Results are treated under five headings. Depending on their importance, the second step started with the detailed description of prominent architectural complex (külliye) and it continued with determination of preservation problems of other waqf buildings recorded in the list. Following stage, results are presented by a schema and rehabilitation proposals were given according to the survey studies. Although a lot of research has been done on Üsküdar, it is a place which offers quantities for new research topics were faced with new questions when we try to examine its structure during a certain period and its evolution through time. Trying to discover the changing face of Üsküdar in terms of waqf property including modest buildings such as fountains to monumental complexes which were built between the 15th and the 20th century brought surprising experiences. The processes of waqf property which represent the cultural heritage of Üsküdar and their interaction with the city give them an independent identity apart from the period they were founded. However existence efforts of these buildings changed during a long historical journey were not weakened the importance of them. Apart from the examples ruined completely or altered, connecting the past and the future is only possible by preserving the changes which include each other as the marks of the past are still dicernable on the buildings. However, the first step of accepting waqf property as the universal values which cannot be damaged by interventions in order to preserve the authenticity of the buildings. To prevent further damages, by means of the historical, physical and even the social structure of the buildings, are only possible by developing integrated conservation proposals for Üsküdar’s Waqf Cultural Heritage within the scope of the internationally acceptable principles.
Uskudar’s Waqf Cultural Heritage And Proposals For It’s Conservation
(Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2011
(PhD) -- İstanbul Technical University, Institute of Science and Technology, 2011
Keywords: İstanbul; Üsküdar; vakıf; kültür mirası; anıt; koruma; Istanbul; Scutari; Uskudar; waqf; cultural heritage; conservation